تقييم فعالية الفبرين الغني بالصفيحات في إغلاق الاتصال الفموي الغاري - أسعد منذر; بيطار وسيم (Latakia University Journal -Medical Sciences Series, 2017)
تهدف هذه الدراسة إلى تقييم فعالية الفبرين الغني بالصفيحات في إغلاق الاتصال الفموي الغاري وذلك خلال شهرين من المتابعة السريرية والشعاعية. بلغت عدد حالات البحث أحد عشر حالة جراحية أنجزت على الجنسين (45.5% ذكور ،54.5 إناث) ممن تعرضوا لانفتاح الجيب الفكي التالي لقلع الأسنان ،حيث تم الإغلاق باستخدام علقة الفبرين التي تم دكها مكان القلع السني الحاوي على الانفتاح وخياطة غشاء الفبرين إلى حواف اللثة فوقها. أظهرت النتائج نجاح الفبرين في إغلاق الانفتاح الفموي الغاري بنسبة 81.8 % مع اختلاطات تالية للعمل الجراحي بلغت وفق التالي: حدث الألم عند المرضى بنسبة 27.3 % ،التورم بنسبة 18.2 % والتفزر بنسبة 18.2 %. نستنتج أن الفبرين الغني بالصفيحات يتمكن عند استخدامه كغشاء وعلقة معاً من إغلاق الانفتاحات التالية للقلع السني مع أعراض سريرية بسيطة و دون علامات شعاعية تدل على التهاب الجيب الفكي اللاحق. The aim of the study was to evaluate the effectiveness of platelet-rich fibrin (PRF) for closer of oroantral communication (OAC) during two months of clinical and radiographical follow-up. Eleven patients of both sexes(45.5% males ,54.5% females) included in this study who had (OAC) after dental extraction. The closer was done by using fibrin clot which was plugged into the alveolar socket of the extraction site that contains the communication, and then we sutured the fibrin membrane to the gingival borders above it. The results revealed that (PRF) can close the oroantral communication successfully in 81.8% of the sample with the following complications :pain 27.3% , edema 18.2% , dehiscence 18.2%. We conclude that platelet-rich fibrin can close oroantral communication that results from dental extraction when it has been used as a clot and membrane together with simple complicated subsequent clinical symptoms and without radiographical signs of inflammation of the maxillary sinus.